2014
DOI: 10.1007/s00247-014-3062-5
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent urinary tract infections in young children: role of DMSA scintigraphy in detecting vesicoureteric reflux

Abstract: DMSA scan had high overall sensitivity and negative predictive value with a low negative likelihood ratio for ruling out high-grade vesicoureteric reflux on MCUG, which may obviate the need of invasive MCUG along with its associated drawbacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Awais et al reported that Tc-99m DMSA scintigraphy has high sensitivity and negative predictive value on patients with high grade VUR (Grade 3 and higher) and also it has benefit of exclusion of high grade VUR (Awais et al, 2015). In our study, as the VUR grade increased, the probability of renal damage in the kidneys was increased.…”
Section: Discussionsupporting
confidence: 57%
“…Awais et al reported that Tc-99m DMSA scintigraphy has high sensitivity and negative predictive value on patients with high grade VUR (Grade 3 and higher) and also it has benefit of exclusion of high grade VUR (Awais et al, 2015). In our study, as the VUR grade increased, the probability of renal damage in the kidneys was increased.…”
Section: Discussionsupporting
confidence: 57%
“…Decreased renal uptake of the isotope suggests acute pyelonephritis or renal scarring [31, 41]. In addition, a DMSA renal scan can detect majority (> 70%) of children with moderate to severe vesicoureteric reflux [41, 102]. The routine uses of this imaging modality is not generally recommended due to the radiation hazard and the cost involved [20].…”
Section: Diagnostic Imaging Studiesmentioning
confidence: 99%
“…The NICE guidelines recommend DMSA renal scan 4 to 6 months after atypical UTI in children under 3 years of age and recurrent UTI in children of any age [84]. It has been suggested that a normal DMSA renal scan may obviate the need for voiding cystourethrogram in children with recurrent UTI [102]. If a DMSA renal scan has to be performed, it should be performed in the acute phase to detect acute pyelonephritis or 4 to 6 months later to assess for renal scarring [2].…”
Section: Diagnostic Imaging Studiesmentioning
confidence: 99%
“…If the acute DMSA is negative, a MCUG is not performed. Some studies have shown a strong correlation between clinically relevant VUR with dilatation and abnormal scintigraphic scans (24,(109)(110)(111)(112)(113); however, other studies have disputed this approach (28,114).…”
Section: Imaging Strategies In Children With Uti and Vurmentioning
confidence: 99%